Kemény István szociológus - Elbert, Márta; Kende, Júlia (Hungary, 2015)
By researching poverty and the life of Roma and Gipsy with a modern approach, István Kemény became a founder of a new sociological school in Hungary. Many of his followers and colleagues became leading researchers in Hungarian sociology, and prominent figures of intellectual and political opposition during the Kádár-regime. His academic research and political activities were regarded as disloyal by the Communist authorities. He was dismissed from academia as a researcher, and teaching was made impossible for him. He was forced to emigrate in 1977. He moved to Paris. In the 1980s he was a correspondent at Radio Free Europe's Hungarian Unit, and gave weekly analyzes of the Hungarian social and political developments for more than a decade. He moved back to Hungary during the regime change, and played an important role in establishing rule of law and democracy in Hungary in the 1990s.

Kemény István a 20. század második felében iskolát teremtett a magyarországi szegénység és a cigányság helyzetének modern szociológiai eszközökkel történő kutatásában. Tanítványai közül sokan nemcsak a magyar szociológia, hanem a Kádár-kori szellemi-politikai ellenzék meghatározó alakjaivá is lettek.
Tudományos munkássága és közéleti szerepvállalása magára vonta a hatalom rosszallását, kutatói állásából elbocsátották, tanári munkáját ellehetetlenítették. 1977-ben emigrációba kényszerült, Párizsba költözött. Az 1980-as években a Szabad Európa Rádió Magyar Osztályának külső munkatársaként rendszeres heti jegyzetekben kommentálta a magyar társadalmi és politikai fejleményeket. A rendszerváltás idején hazaköltözött, és fontos szerepet játszott az új magyar demokrácia szellemi és szakmai megalapozásában.
Keywords: Documentary films